2014
DOI: 10.1002/tox.22034
|View full text |Cite
|
Sign up to set email alerts
|

8‐Hydroxy‐2′‐deoxyguanosine as a biomarker of oxidative DNA damage induced by perfluorinated compounds in TK6 cells

Abstract: 8-Hydroxy-2'-deoxyguanosine (8-OHdG) is the most common biomarker of oxidative DNA damage, it is formed by chemical carcinogens and can be measured in any species. Perfluorooctanoic acid (PFOA) and perfluorononanoic acid (PFNA) are suspected genotoxic carcinogens through induction of reactive oxygen species that are responsible for oxidative DNA damage. This study was conducted to investigate the in vitro genotoxicity of PFOA and PFNA in human lymphoblastoid (TK6) cell line. TK6 cells were exposed to PFOA at 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The levels of 8‐isoprostane after DSS administration were significantly higher in the Mn‐deficient than in the Mn‐adequate mice (Figure H), indicating that Mn protects against lipid peroxidation in this mouse colitis model. The 8‐OHdG biomarker is excreted during the repair of DNA damage, thereby providing a quantitative index of oxidative DNA damage . The 8‐OHdG levels were significantly increased in the serum of Mn‐deficient mice after DSS injury (Figure I), indicating that Mn protects against oxidative stress‐associated DNA damage in this mouse colitis model.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The levels of 8‐isoprostane after DSS administration were significantly higher in the Mn‐deficient than in the Mn‐adequate mice (Figure H), indicating that Mn protects against lipid peroxidation in this mouse colitis model. The 8‐OHdG biomarker is excreted during the repair of DNA damage, thereby providing a quantitative index of oxidative DNA damage . The 8‐OHdG levels were significantly increased in the serum of Mn‐deficient mice after DSS injury (Figure I), indicating that Mn protects against oxidative stress‐associated DNA damage in this mouse colitis model.…”
Section: Resultsmentioning
confidence: 92%
“…The 8-OHdG biomarker is excreted during the repair of DNA damage, thereby providing a quantitative index of oxidative DNA damage. 21 The 8-OHdG levels were significantly increased in the serum of Mn-deficient mice after DSS injury Figure 4I), indicating that Mn protects against oxidative stress-associated DNA damage in this mouse colitis model. Mn deficiency, therefore, reduced cellular MnSOD activity and increased oxidative stress in the mouse model of DSSinduced colitis.…”
Section: Mn Deficiency Induces Oxidative Damage After Dss Treatmentmentioning
confidence: 88%
“…In fact, PFOA and PFNA are suspected genotoxic carcinogens through induction of reactive oxygen species that are responsible for oxidative DNA damage. Recently, Yahia et al 49 demonstrated that PFOA and PFNA induced DNA damage in TK6 cells, observing that PFNA produced high levels of 8-hydroxy-2′-deoxyguanosine (8-OhdG), a biomarker of oxidative DNA damage. In contrast, in experiment 2, all PFAS substances caused alterations associated with secondary structures of proteins (Amide I, Amide II, and Amide III) (see Figure S2 and Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…DMSO is a known scavenger of free radicals and can protect DNA from oxidative damage 94 . In human lymphoblastoid TK6 cells, exposure to 0.25 or 0.5 mg/mL PFOA for 2 hours produced small but significant increases in DNA damage in the comet assay and in 8hydroxy-2ʹ-deoxyguanosine DNA adducts (per 10 5 dG) as detected using high-performance liquid chromatography (HPLC)-mass spectrometry (MS) 95 . Similar results were obtained for PFNA when tested at 0.125 or 0.25 mg/mL 95 .…”
Section: Genetic Toxicitymentioning
confidence: 99%
“…In human lymphoblastoid TK6 cells, exposure to 0.25 or 0.5 mg/mL PFOA for 2 hours produced small but significant increases in DNA damage in the comet assay and in 8hydroxy-2ʹ-deoxyguanosine DNA adducts (per 10 5 dG) as detected using high-performance liquid chromatography (HPLC)-mass spectrometry (MS) 95 . Similar results were obtained for PFNA when tested at 0.125 or 0.25 mg/mL 95 . Exposure to PFOA at concentrations up to 300 µM for 5 or 24 hours did not induce DNA damage in Syrian hamster embryo cells as measured using the comet assay 96 .…”
Section: Genetic Toxicitymentioning
confidence: 99%